The Implementation of Practice Based Simulation of New Nurse Toward Self Confidence: A Literature Review - Baso, Yusriani Saleh; Arofiati, Fitri (Journal Of Nursing Practice, 2020)
Background: To enhance the quality of nursing service at hospital, it needs learning process (education and training) using clinical skills facility. It gives ideal place for the development of nurseâ€™s confident before entering the real world of work. Problem based learning approach is able to use simulation learning method or Practice Based Simulation Model can enhance new nurseâ€™s confidence. Objective: This study aimed at investigating the literature for of the practice based simulation that may be expected to enhance new nurseâ€™s self confidenceMethod: This research used Literature Review. Source of the research was taken from some database. Searching was conducted in December 2018 through database of PubMed of 3016 articles, Google Scholar of 13.5000 articles, Science Direct of 3466 articles, Pro Quest of 256 articles using combination of key words â€œself confidenceâ€ and practice based simulation+new graduates nursing. From all database, there were only 7 which fulfilled inclusion criteria.Result: based on the result of literature review from 7 articles, it was found that applying simulation method to new nurse can enhance self confidence. New nurse would be more independent, able to make decision and conduct nursing care and be more calm while working.Conclusion: the aim of this literature review obtains the result that application of practice based simulation can increase self confidence of nurse.